THE TREATMENT OF IMMUNE, CYTOKINE AND ANTIOXIDANT STATUS DISORDERS IN PATIENTS WITH CHRONIC SALPINGOOPHORITIS - A. A. Konoplya; S. V. Petrov; V. P. Gavrilyuk (Медицинская иммунология)
Abstract. A number of studies provide evidence for significant disturbances of immune, cytokine and antioxidant conditions in the patients with chronic salpingoophoritis. The own studies of combined effects produced by some medications, with respect to correction of altered laboratory parameters in such patients, have shown higher efficiency of ridostine/lipoic acid combination, as compared to derinate/tocopherol treatment. The revealed correlations between the clinical signs and immune status of the patients with a salpingoophoritis, suggest that only some of immunological parameters could be used for predictive purposes. The established positive influence of studied drugs on the disturbed functions of immune and antioxidant systems suggests a need to introduce immunocorrector drugs and antioxidants into complex therapy of the patients by chronic salpingoophoritis.